PENGARUH SIKAP, BRAND CONSCIOUSNESS, PERSEPSI NILAI DAN PRIVATE LABEL BRAND IMAGE PADA NIAT KONSUMEN DALAM MEMBELI PRODUK PRIVATE LABEL BRAND - , Sutriani; , Ike Janita Dewi, Dr., M.B.A. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Developing the Private Label Brand is a strategy set by retailers to achieve higher profitability. This Private Label Brand is a product brand whose name is taken from the name of the retailer. Hence, researcher wanted to know the influence of attitudes, brand consciousness, perception of value and Private Label Brand image on consumer intention to buy the Private Label Brand product. This study was conducted at three retail stores located in Yogyakarta that is Carrefour, Superindo, and Giant. Total samples of this study were 450 respondents, consisted from 150 consumers of Carrefour, 150 consumers of Superindo, and 150 consumers of Giant. The non-probability sampling was used in this study